Statin use is associated with reduced incidence and progression of knee osteoarthritis in the Rotterdam study. Issue 5 (11th October 2011) - Clockaerts, S; Van Osch, G J V M; Bastiaansen-Jenniskens, Y M; Verhaar, J A N; Van Glabbeek, F; Van Meurs, J B; Kerkhof, H J M; Hofman, A; Stricker, B H Ch; Bierma-Zeinstra, S M
Abstract : Background: Osteoarthritis is the most frequent chronic joint disease causing pain and disability. Besides biomechanical mechanisms, the pathogenesis of osteoarthritis may involve inflammation, vascular alterations and dysregulation of lipid metabolism. As statins are able to modulate many of these processes, this study examines whether statin use is associated with a decreased incidence and/or progression of osteoarthritis. Methods: Participants in a prospective population-based cohort study aged 55 years and older (n=2921) were included. x-Rays of the knee/hip were obtained at baseline and after on average 6.5 years, and scored using the Kellgren and Lawrence score for osteoarthritis. Any increase in score was defined as overall progression (incidence and progression). Data on covariables were collected at baseline. Information on statin use during follow-up was obtained from computerised pharmacy databases. The overall progression of osteoarthritis was compared between users and non-users of statins. Using a multivariate logistic regression model with generalised estimating equation, OR and 95% CI were calculated after adjusting for confounding variables. Results: Overall progression of knee and hip osteoarthritis occurred in 6.9% and 4.7% of cases, respectively. The adjusted OR for overall progression of knee osteoarthritis in statin users was 0.43 (95% CI 0.25 to 0.77, p=0.01). The use of statins was not associated with overall progression of hip osteoarthritis. Conclusions: Statin use is associated with more than a 50% reduction in overall progression of osteoarthritis of the knee, but not of the hip.